KINETIKA FERMENTASI ASAM ASETAT (VINEGAR) OLEH BAKTERI Acetobacter aceti B 127 DARI ETANOL HASIL FERMENTASI LIMBAH CAIR PULP KAKAO [Kinetics of Acetic Acid (Vinegar) Fermentation By Acetobacter aceti B127 from Ethanol Produced by Fermentation of Liqu - M. Supli Effendi (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2002)
Acetic acid concentration is one of vinegar’s quality parameter. Acetic acid concentration in vinegar is influenced by the activity of acetic acid bacteria. This research studied the kinetics of anaerobic fermentation of liquid waste of cacao pulp by Saccharomyces cerevisiae R60 to produce ethanol and the kinetics of acetic acid fermentation from ethanol by Acetobacter aceti B127. The kinetics of acetic acid fermentation from ethanol by Acetobacter aceti B127 can be used as a basic of bioprocess design for aerobic fermentation in general and acetic acid fermentation from ethanol by Acetobacter aceti B127 in particular. Fermentation medium used was liquid waste of cocoa pulp with sugar content of 12.85%, and the addition of sucrosa and urea. The parameter observed was growth of Saccharomyces cerevisiae R60 and Acetobacter aceti B127, and chemical analysis including concentration of ethanol, total sugar and acetic acid, content. The research result showed that the m value was 0.048 hour-1, Y P was 0.676, Qp value was 0.033 hour-, and KLa value was 0.344, QO2.Cx value was 0.125 (mgO2L-1jam-1), Y X was sO20.378 (x 108selmL-1g-1O2), and dCT was 0.150 mgL-1hour-1. Concentration of acetic acid in the product was 4.24% or 42.4 gL-1 dt.